Hubungan Siklus Menstruasi terhadap Tingkat Keparahan Jerawat (Acne Vulgaris) pada Remaja Putri - Liana Aldayana; Hernandia Distinarista; Apriliani Yulianti Wuriningsih; Sri Wahyuni (Journal of Medical Practice and Research, 2025)
This study aimed to analyze the relationship between menstrual cycle regularity and the severity of acne vulgaris among adolescent girls. A quantitative cross-sectional design was applied involving 121 female students who had experienced menarche. Data were collected using structured questionnaires assessing menstrual cycle patterns and acne severity. Univariate analysis described respondent characteristics, while bivariate analysis using Somers’ d test examined the association between variables at a significance level of 0.05. The findings showed that more than half of the respondents had irregular menstrual cycles and most experienced moderate to severe acne vulgaris. Statistical analysis revealed a significant positive association between irregular menstrual cycles and increased acne severity. These results indicate that hormonal fluctuations reflected by menstrual cycle irregularity play an important role in the pathogenesis of acne vulgaris during adolescence. Understanding menstrual cycle patterns may therefore contribute to more effective preventive and management strategies for acne vulgaris among adolescent girls. The study provides empirical evidence supporting the integration of reproductive health considerations into adolescent dermatological care.